(untitled) (Conferencea, 2023)
The main content of this scientific article is the study of the existing problems in the teaching of subjects in higher education institutions and their analysis, as well as the practical application of methods and tools aimed at solving the problems. Detailed information is provided on effective work on the development of modern software tools and organization of the educational process based on today’s demands and pedagogical technologies in the teaching of subjects.